Negosiasi Standar Kecantikan dan Citra Tubuh Mahasiswi Muslim; Studi pada Mahasiswa IAIN Sultan Amai Gorontalo - Nuraisah; Andi Oktami Dewi Artha Ayu Purnama; Sunandar Macpal (LPPM IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the negotiation of digital beauty standards and body image formation among female students at IAIN Sultan Amai Gorontalo. The study is grounded in the increasing exposure to beauty, lifestyle, skincare, fashion, and ideal-body content on Instagram and TikTok, which encourages young women to evaluate their bodies through visual standards circulating in digital spaces. This research employed a descriptive qualitative method with a sociological approach. The participants consisted of six active female students aged 18-24 years who actively used Instagram and/or TikTok. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the Miles, Huberman, and Saldana model, including data reduction, data display, and conclusion drawing. The findings show that digital beauty standards are not accepted in a single and passive manner by participants. Instead, they are negotiated through understanding, social comparison, pressure to follow trends, consumption of beauty products, body management, and critical awareness of social media realities. Some participants experienced body dissatisfaction and declining self-confidence after comparing themselves with influencers, celebrities, or other social media users. However, others used social media as a source of motivation for self-care, self-acceptance, and a broader understanding of beauty beyond physical appearance. This study confirms that body image among female students is formed through the interaction between digital beauty standards, social experiences, and digital literacy in filtering social media content.